Pelatihan Dharmagita untuk Meningkatkan Kemampuan Generasi Muda Hindu Melantunkan Dharmagita - Ni Nyoman Sudiani; Utami, Dian Syanita; Sevriyani, Komang Evi; Murtini, Komang; Natali, Ni Putu Desi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Dharmagita is a sacred song that serves to spread the teachings of the Vedas. The Vedic teachings were received by the Maharsis through sacred words. Maharsi then implemented the teachings of dharma to the people through the Gita. Vedic teachings consist of verses and are conveyed by singing them. Dharmagita turns out to be a very effective method for implementing Hindu teachings, especially among the younger generation. Therefore, it is very important to improve the ability of dharmagita among the younger generation. The Hindu Dharma Nusantara College feels responsible for improving the dharmagita abilities of the younger generation so that it carries out community service activities. The aim of this PkM is to improve the ability to read sloka and kakawin of the younger generation. This activity was carried out at the Dharmasevanam Aditya Jaya Rawamangun Building. The trained participants consisted of pasraman students from all over DKI Jakarta for children and teenagers. The method used is training with pretest and post test. The results of this service were that the ability to read sloka and kakawin of pasraman students increased, but not yet significantly. This activity must be carried out regularly so that satisfactory results are obtained. Keywords: training; dharmagita; young generation of Hindus